2012
DOI: 10.1016/j.jpainsymman.2011.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Experience of Care in Women With Metastatic Breast Cancer: A Cross-Sectional Survey

Abstract: Context. Despite developments in the medical management of metastatic breast cancer, little is known about the quality of life (QoL) and experience of care in women with it.Objectives. To explore QoL, experience of care, and support needs of women living with metastatic breast cancer in the U.K.Methods. Questionnaire-based, cross-sectional study, undertaken in two U.K. cancer centers and online via the Breast Cancer Care Web site, assessing QoL and experience of care in 235 women with metastatic breast cancer.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
57
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 10 publications
5
57
1
1
Order By: Relevance
“…Declines in quality of life and disease-related symptoms have been observed [4][5][6]. However, the physical status of this population remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Declines in quality of life and disease-related symptoms have been observed [4][5][6]. However, the physical status of this population remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The CCEQ covers a broad range of experiences, which have been identified as important to patients living with chronic cancer 3 6. It assumes that patients with chronic cancer have an ongoing and predominantly outpatient relationship with hospital-based oncology services, with supplementary involvement from primary care and community or palliative care services, as described in previous research 3 6.…”
Section: Discussionmentioning
confidence: 99%
“…Very little is known about patients' experiences of chronic cancer. For women with advanced breast cancer, research has shown that satisfaction with experience of care is poor, that care is predominantly in the hospital setting and there is little evidence of involvement of general practitioners (GPs) or palliative care services 6. Prior research by the authors, interviewing 56 patients living with chronic cancer (breast, gynaecological, colorectal, renal and prostate cancers), identified that patients experience a range of problems, including difficulty managing treatment schedules and frequent hospital appointments; a lack of integration between hospital and community/general practice services; difficulty coping with multiple and changing symptoms alongside the cyclical nature of chronic cancer; and difficulty dealing with uncertainty 3…”
Section: Introductionmentioning
confidence: 99%
“…support from health care professional Reed et al [29] conducted a questionnaire-based, crosssectional study, in two U.K cancer centres and online via the Breast Cancer Care website, assessing Quality of Life and the experience of care in 235 women with metastatic Breast Cancer. Overall, the results showed that the patients' satisfaction with their experience of care, including psychological and emotional care, was low.…”
Section: Family Support Vsmentioning
confidence: 99%